2021
DOI: 10.1002/ansa.202000160
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopy in breast cancer metabolomics

Abstract: Breast cancer poses a significant health care challenge worldwide requiring early detection and effective treatment strategies for better patient outcome. A deeper understanding of the breast cancer biology and metabolism may help developing better diagnostic and therapeutic approaches. Metabolomic studies give a comprehensive analysis of small molecule metabolites present in human tissues in vivo. The changes in the level of these metabolites provide information on the complex mechanism of the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 107 publications
(566 reference statements)
0
2
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS) are the two analytical techniques most often used in metabolomics. The analysis of metabolites in blood and other biological samples allows the detection of even subtle changes related to the development of a disease, including BC (5)(6)(7)(8)(9). Several studies reported that serum/plasma metabolome profiling could be used to provide signatures associated with a risk of BC.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS) are the two analytical techniques most often used in metabolomics. The analysis of metabolites in blood and other biological samples allows the detection of even subtle changes related to the development of a disease, including BC (5)(6)(7)(8)(9). Several studies reported that serum/plasma metabolome profiling could be used to provide signatures associated with a risk of BC.…”
Section: Introductionmentioning
confidence: 99%
“…In another review on the application of magnetic resonance spectroscopy (MRS) in breast cancer, Sharma and Jagannathan 9 compare the technology with mass spectrometry and demonstrate a handful of applications in biomedical research, which goes on to show its enormous potential in capturing the underlying metabolic reprogramming in breast cancer cells, in unravelling molecular biomarkers, and applications in in vitro and ex vivo studies.…”
mentioning
confidence: 99%